Paisagem e percepção da paisagem: estudos de caso na Austria e no Brasil - Serpa, Angelo (Paisagem e Ambiente, 1995)
The most important point of this discussion is the question, how the increasing gap between aesthetic production and aesthetic perception in landscape architecture could be bridged and how landscape architects could contribute to overcome this gap with their professional means. From this point of view, various methods for the improvement of the quality of communication between experts and other participants of a planning process are discussed. In the first part simulation models are presented, which have been developed for the determination of optical and aesthetical effects of plants structures. The main topic of the second part are the “inner landscapes” of planners and their clients. The question is, how individual experiences of experts and clients influence the perception of their environment and how these experiences could be described. According to the ideas of C. G. Jung the meaning of both archetypic images and individual experiences during the adoption of a landscape are investigated with the help of a sample of 40 interviews. In the third part the steps from individual to collective experiences are demonstrated using one example of social movement in Brazil: The approach of members of the Candomblé religion to “their” park in Salvador da Bahia